(untitled) (New York, 1995)
This book provides a broader view of abstraction, complexity, data structures, software design, and their underlying principles. in addition, the integrated laboratory experience provides a rich exposure to the principles of object-oriented software design, with an emphasis on data structures, data abstraction, team programming, and their applications in operating systems and compiler design.
Keywords: Electronic data processing